Considerations on the water supply of the aquifer-wetland systems in Colombia from the GRACE satellites data interpretation - Bolaños-Chavarría, Silvana (2022)
[Introduction]: Thanks to the recent data provided by the GRACE satellites, it is possible to establish a prelimi- nary estimate of changes in groundwater storage (GWS), thus offering a new and unprecedented tool for studying the dynamics of aquifer-wetland systems. [Objective]: As a result of the trends observed in GRACE for the Magdalena-Cauca basin in Colombia, this study investigates the water availability of the aquifer-wetland systems. [Methodology]: For this purpose, a map overlay analysis was performed using GRACE data to estimate ground- water recharge and discharge for different basins and aquifer-wetland systems. [Results]: Considering the trends in groundwater storage (GWS), we obtained water volumes and translated these into recharge and discharge esti- mates of the aquifer-wetland systems identified in the Magdalena-Cauca basin. These values show a total recharge between 2002 and 2010 of 284.65 mm, followed by a loss of 490.68 mm between 2011 and 2017. Furthermore, good correspondence was observed between the ENSO and GWS events, especially during the strong 2010-2011 La Niña and 2015-2016 El Niño events, which caused severe impacts in the country and that were particularly evi- dent in the Mojana wetland area located in the north of the basin. [Conclusions]: Although these results have yet to be validated with continuous monitoring data, the results presented in this study raise questions on the formulation of better policies and management of water resources that promote future water security.